EU climate change policy 2013-2020: using the clean development mechanism more effectively - Gorecki, Paul K.; Lyons, Seán; Tol, Richard S.J. (Dublin, 2009)
"Under European Union proposals for CO2 emission reduction between 2013 and 2020, a Member State can transfer to another Member State the right to use its unused Clean Development Mechanism (“CDMs”) credits. The paper addresses three issues in relation to these CDM Warrants (“CDMW”). First, how should the Member State treat the CDMW in making decisions concerning emission reduction? The price of the property right is an important signal for a Member State in deciding the level of domestic abatement compared to trading in CDMWs. In other words, a shadow price for CDMWs should be used in formulating the emission strategy in order to determine whether or not a member State is a buyer or seller of CDMWs. Second, what mechanism should be used to facilitate the exchange of CDMWs? The preferred mechanism depends on the market size, over which there appears to be some ambiguity: market intermediaries such as Over-the-Counter trades and exchanges are preferred if market size is small; auctions if the market size is large. Third, who should realise the value of CDMWs – the State, existing polluters etc? The value of CDMWs should accrue to the State."